Contemporary Antiviral Drug Regimens for the Prevention and Treatment of Orolabial and Anogenital Herpes Simplex Virus Infection in the Normal Host: Four Approved Indications and 13 Off-Label Uses - Fred Y Aoki (Canadian Journal of Infectious Diseases)
Herpes simplex virus (HSV) orolabial and anogenital infection causes substantial and recurring disease in healthy individuals due directly to infection of these sites and, indirectly, due to its complications. These complications include eczema herpeticum plus erythema multiforme and neonatal HSV infection, respectively. Four drugs: acyclovir, famciclovir, valacyclovir and penciclovir, are currently licensed by the Therapeutics Products Directorate of Health Canada for the management of HSV infections. Although these drugs are only approved for four orolabial and anogenital infections in healthy persons, their efficacy and safety for 13 other related uses in this population have been demonstrated in controlled clinical trials, so called off-label uses. In this review, the evidence supporting these 17 uses, the drugs and regimens evaluated, and their current costs, are described.